Genetic Variants of Neurotransmitter-Related Genes and miRNAs in Egyptian Autistic Patients - Ahmed M. Salem; Samira Ismail; Waheba A. Zarouk; Olwya Abdul Baky; Ahmed A. Sayed; Sawsan Abd El-Hamid; Sohair Salem (The Scientific World Journal)
Autism is a neurodevelopmental disorder with indisputable evidence for a genetic component. This work studied the association of autism with genetic variations in neurotransmitter-related genes, including MAOA uVNTR, MAOB rs1799836, and DRD2 TaqI A in 53 autistic patients and 30 healthy individuals. The study also analyzed sequence variations of miR-431 and miR-21. MAOA uVNTR was genotyped by PCR, MAOB and DRD2 polymorphisms were analyzed by PCR-based RFLP, and miR-431 and miR-21 were sequenced. Low expressing allele of MAOA uVNTR was frequently higher in female patients compared to that in controls (OR = 2.25). MAOB G allele frequency was more significantly increased in autistic patients than in controls (P<0.001 for both males and females). DRD2 A1+ genotype increased autism risk (OR = 5.1). Severity of autism tends to be slightly affected by MAOA/B genotype. Plasma MAOB activity was significantly reduced in G than in A allele carrying males. There was no significant difference in patients and maternal plasma MAOA/B activity compared to controls. Neither mutations nor SNPs in miR-431 and miR-21 were found among studied patients. This study threw light on some neurotransmitter-related genes suggesting their potential role in Autism pathogenesis that warrants further studies and much consideration.